THE ORIGIN OF THE WORD “MOTHER” (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article presents the origin of the mother lexeme and its expression in other languages. In the framework of related and non-related languages, the comparative and comparative plan is covered with factual examples.